(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The temples in India stand for the cultural symbols which talk about the egalitarian principle of the Tamils. This symbolizes that all are born equal. The sculptures, paintings and artifacts of the temple tell about the daily life activities which reveal the historic resources of the early treasures. This speaks about the three aspects in Tamil language which are known to be literature, drama and music. The Hindu Religions and Charitable Endowments Boards as later formed and developed as a department entrusted with the responsibilities of maintaining the temples and also conducting the poojas and the festivals in keeping with the practices of the ancient culture and norms.